The Impact of Value over Innovation - Masuoka, Toru (2009)
This dissertation is based on the group report (Thaper et al, 2009), which is the output from a leading pharmaceutical company commissioning a team of Nottingham University MBA students to investigate the potential of unmet demand in the pharmaceutical market. Based on the investigation undertaken, the report produced a series of recommendations which could help a leading pharmaceutical company to create value for customer. This dissertation investigates whether the type of value the company pursues influence the type of innovation it undertakes. The research identifies four main types of value (Consumer values and consumer value; Augmented product concept; Customer satisfaction and service quality; and The value chain) as well as five types of innovation (Product; Process; Position; Paradigm Type A; and Paradigm Type B). The author investigates the influence of the type of value the company pursues over the type of innovation it undertakes. The research studies four carefully selected cases to identify any relationships/links between the type of value the company chooses and the type of innovation it undertakes. The results show that companies pursue multiple types of value in parallel. All businesses in the cases pursued „The Value Chain‟ whilst pursuing additional type(s) of value depending on the business. It also indentifies some links between the types of value and the types of innovation the company undertaken. On reflection of these results, the author applies the framework to recommendations from Thaper et al. The author analyzes the implication of each recommendation in terms of innovation target(s) for a leading pharmaceutical company. Then the author uses this information to propose the types of value a leading pharmaceutical company should pursue in order to implement recommendations in Thaper et al.